2020
DOI: 10.3390/su12073048
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Indications and Price Volatility Dynamics of Lamb Prices in Spain

Abstract: For decades, food quality standards have attracted the interest of governance institutions and regulation authorities, who have responded to the increasing and demanding societal challenges. In addition, the open debate on significant variability and unusually high levels of agrifood prices recorded in 2007 and later in 2011 affect the behavior of the chain actors involved. As an attempt to bring together these wide concerns within a quantitative framework, a comparative analysis of the performance of the pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…These data highlight the need to develop measures and policy responses to help producers fight price volatility [13,33,34,36,37]. In this regard, the efficiency degree of the markets is also important in order to adopt stabilizing measures that can dissipate any shocks with no degree of persistency of volatility [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data highlight the need to develop measures and policy responses to help producers fight price volatility [13,33,34,36,37]. In this regard, the efficiency degree of the markets is also important in order to adopt stabilizing measures that can dissipate any shocks with no degree of persistency of volatility [17].…”
Section: Discussionmentioning
confidence: 99%
“…This recognition could help producers to better market their products [15,16]. In this sense, recent data suggested that PGI may be an efficient tool to protect lamb farmers from fluctuating prices, thus assuring the fulfillment of positive externalities [17]. Moreover, the role of agrarian markets around the country, which set weekly meat prices and are also used as reference for commercial transactions [18], could also be the reason for price differences.…”
Section: Introductionmentioning
confidence: 99%
“…It has gained ore interest since its protection has been ensured multilaterally under the Trade-Related Aspects of Intellectual Property Rights (TRIPS) Agreement of the World Trade Organisation. (Singh, 2016;Ferrer-Pérez, 2020) For almost 30 years, the European Union (EU) has introduced legislation for the protection of geographical indications for agricultural products and foodstuffs, as an instrument for an active quality policy (Josling, 2006, Leufkens, 2018.…”
Section: Review Of the Scientific Literaturementioning
confidence: 99%
“…The results from Barjolle and Sylvander [22] show that the economic success of registered products in comparison to similar, unregistered products depends in particular on the specificity of the product, its relevance for the market, and cooperation between members of the protection associations. Most recently, Ferrer-Pérez et al [34] show at the example of the Navarra lamb the potential of protecting regional farmers from strongly fluctuating prices with GI measures.…”
Section: Price-related Argumentsmentioning
confidence: 99%